Prediction of Solar Resource and Photovoltaic Energy Production through the Generation of a Typical Meteorological Year and Meso-NH Simulations: Application to the South of Portugal - Pereira, Sara (2020)
The goal of this work is the generation of solar resource and photovoltaic (PV) energy maps based on simulations of a Numerical Weather Prediction model (NWP) for a Typical Meteorological Year (TMY). This approach is applied to the South of Portugal. Sixteen years of observations were used to determine a TMY for the city of Évora, which is located near the center of the region, through the Sandia method and the Finkelstein-Schafer statistics. The NWP Meso- NH model, with the ecRad radiation scheme integrated, is used to simulate the TMY, allowing for the generation of solar resource and air temperature maps that are helpful in predicting PV potential, thus constituting a useful tool for planning and designing this type of solar systems.